Selected Indonesian Medicinal Plants for the Management of Metabolic Syndrome: Molecular Basis and Recent Studies - Arozal, Wawaimuli; Louisa, Melva; Soetikno, Vivian (Frontiers in Cardiovascular Medicine, 2020)
Increased prevalence of metabolic syndrome (MetS) in the world influences quality of health in all respective countries, including Indonesia. Data from Indonesian Family Life Survey reported in 2019 showed that the prevalence of MetS in Indonesia currently is 21.66%, estimated with the provincial incidence ranging up to 50%; additionally, the most common components of MetS discovered in Indonesia were poor high-density lipoprotein (HDL) cholesterol and hypertension. Management treatment of MetS involves a combination of lifestyle changes and pharmacological interventions to decrease cerebrovascular disease. Various natural substances have been shown to govern any cardiovascular or metabolic disorders through different mechanisms, such as triggering anti-inflammation, lipid profile correction, sensitization of insulin reception, or blood glucose control. In Indonesia, the utilization of natural compounds is part of the nation's culture. The community widely uses them; even though in general, their effectiveness and safety have not been thoroughly assessed by rigorous clinical trials. Scientific evidence suggested that cinnamon, mangosteen, and curcumin, as well as their derived components possess a broad spectrum of pharmacological activity. In this review, an enormous potential of cinnamon, mangosteen, and curcumin, which originated and are commonly used in Indonesia, could treat against MetS, such as diabetes, hyperlipidemia, hypertension, and obesity. The findings suggested that cinnamon, mangosteen, curcumin and their derivatives may reflect areas of promise in the management of MetS.